PROBLEM ISSUES OF THE QUALITY OF THE SYSTEM OF PRE0PROFESSIONAL TRAINING: PSYCHOLOGICAL, EDUCA0 TIONAL AND ECONOMIC ASPECTS - Moskalyk, G. F. (Continuing Professional Education: Theory and Practice, 2019)
G.F. Moskalyk’s work “Problem issues of the quality of the system of preprofessional training: psychological, educational and economic aspects” is devoted to the analysis of the main problems of implementation of preprofessional training in the secondary school. In the work the attempt was made to define the principles of professional determination of schoolleavers, to identify conditionality of choice of profile learning in the secondary school based on regional historical, economic and geographic traditions, to develop criteria for the effective implementation of the system of preprofessional training in the educational district, to make recommendations for the development of regional programs of social and economic developmentto the executive power and local authorities.The attempt to develop criteria for weighing the achievements and impact of the introduction of preprofessional training in the educational district was also made.